2020
DOI: 10.1002/jat.4112
|View full text |Cite
|
Sign up to set email alerts
|

α‐Asarone, β‐asarone, and γ‐asarone: Current status of toxicological evaluation

Abstract: Asarone isomers are naturally occurring in Acorus calamus Linné, Guatteria gaumeri Greenman, and Aniba hostmanniana Nees. These secondary plant metabolites belong to the class of phenylpropenes (phenylpropanoids or alkenylbenzenes). They are further chemically classified into the propenylic trans-and cis-isomers α-asarone and β-asarone and the allylic γ-asarone.Flavoring, as well as potentially pharmacologically useful properties, enables the application of asarone isomers in fragrances, food, and traditional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 52 publications
0
33
0
1
Order By: Relevance
“…β-asarone extracted from the root bark of Cordia alliodora has shown a minimal concentration of 25 µg/mL to kill all tested larvae (Ioset et al, 2000) and at LC 50 value of 26.99 µg/mL from Asarum heterotropoides roots (Perumalsamy et al, 2009). However, asarone isomers have demonstrated mammalian carcinogenic effects (Haupenthal et al, 2017, Uebel et al, 2020. On the other hand, myristicin was found to be one of the major components in P. permucronatum (25.61%) and P. hostmanianum (20.26%) (de Morais et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…β-asarone extracted from the root bark of Cordia alliodora has shown a minimal concentration of 25 µg/mL to kill all tested larvae (Ioset et al, 2000) and at LC 50 value of 26.99 µg/mL from Asarum heterotropoides roots (Perumalsamy et al, 2009). However, asarone isomers have demonstrated mammalian carcinogenic effects (Haupenthal et al, 2017, Uebel et al, 2020. On the other hand, myristicin was found to be one of the major components in P. permucronatum (25.61%) and P. hostmanianum (20.26%) (de Morais et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…[24][25][26][27] However, toxicological studies suggested it possess carcinogenicity and genetic toxicity. 28,29 Apparently, in this sense, it's not reasonable to view b-asarone as the representative neuroprotective constituent of A. calamus. Therefore, it is necessary to evaluate the neuroprotective bioactivities of other types of compounds.…”
Section: Introductionmentioning
confidence: 99%
“…According to relevant literature reports and pharmacopoeia's main pharmacological effects and main drug components, we found that the common component is the main substance to exert efficacy. There are 54 common components in ATS and KXS, such as β-asarone, α-asarone, γ-asarone, methyleugenol, linalool, camphor and methyl eugenol are the main effective components in the treatment of amnesia 31.…”
mentioning
confidence: 99%
“…Existing studies have shown that isocalamenediol, α-asarone, β-asarone, methyl eugenol, isoeugenol methyl ether, camphor, anethol, 2,4-di-tert-butylphenol, linalool, and asarylaldehyde are the 10 main medicinal components in KXS VOCs which have good medicinal effects. For example, β-asarone and α-asarone have good effects as antidepressants, and in the treatment of anti-senile dementia and memory improvement; methyl eugenol has anesthetic effects 31,37. For the reason that quantitative analysis of the main volatile medicinal substances which provides a basis for the study of the medicinal substance basis of KXS.…”
mentioning
confidence: 99%